THE RELATIONSHIP OF NUTRITIONAL KNOWLEDGE AND MICRONUTRIENT INTAKE WITH THE EVENT OF ANEMIA IN PREGNANT WOMENCOVID-19 PANDEMIC (Case Study In The Work Area Of Tapa Health Center, Bone Bolango Regency) - Pratiwi Hulinggi; Sunarto Kadir; Tri Septian Maksum (Journal Health & Science : Gorontalo Journal Health and Science Community, 2023)
AbstrakAnemia pada ibu hamil berdampak pada tidak optimalnya pertumbuhan dan perkembangan janin dalam kandungan serta berpotensi menimbulkan komplikasi kehamilan dan persalinan, bahkan menyebabkan kematian ibu dan anak. Kebaruan penelitian ini karena menganalisis hubungan pengetahuan gizi dan asupan mikronutrien dengan kejadian anemia pada ibu hamil di masa pandemi covid-19. Tujuan penelitian adalah untuk menganalisis hubungan pengetahuan gizi dan asupan mikronutrien dengan kejadian anemia pada ibu hamil di masa pandemi Covid-19 di Puskesmas Tapa Kabupaten Bone Bolango. Penelitian ini merupakan penelitian observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil yang ada di Wilayah Kerja Puskesmas Tapa Kabupaten Bone Bolango. Teknik pengambilan sampel menggunakan accidental sampling sehingga sampel dalam penelitian ini  sebanyak 31 ibu hamil. Data dianalisis menggunakan uji chi square. Instrumen penelitian pengetahuan menggunakan kuesioner dan asupan mikronutrien menggunakan food recall 24 jam untuk memudahkan responden yang buta huruf. Hasil penelitian menunjukkan bahwa paling banyak responden berpengetahuan baik (58,1%), asupan mikronutrien (zat besi, asam folat dan zink) dalam kategori sesuai (77,4%), tidak mengalami anemia (74,2%). Kesimpulan bahwa ada hubungan pengetahuan gizi dan asupan mikronutrien dengan kejadian anemia pada ibu hamil di masa pandemi Covid-19 di Puskesmas Tapa Kabupaten Bone BolangoKata Kunci: Pengetahuan gizi; Asupan mikronutrien; Anemia; Ibu Hamil; Pandemi covid-19. AbstractAnemia in pregnant women impacts the non-optimal growth and development of the fetus in the womb. It can potentially cause pregnancy and childbirth complications and even cause maternal and child death. This study's novelty is that it analyzes the relationship between nutritional knowledge and micronutrient intake with the incidence of anemia in pregnant women during the Covid-19 pandemic. The study aimed to explore the relationship between nutritional knowledge and micronutrient intake with the incidence of anemia in pregnant women during the Covid-19 pandemic at the Tapa Health Center, Bone Bolango Regency. This study is an observational study with a cross-sectional approach. The population in this study was all pregnant women in the Tapa Health Center Working Area, Bone Bolango Regency. The sampling technique used accidental sampling so that the samples in this study were 31 pregnant women. The data were analyzed using the chi-square test. The knowledge research instrument uses questionnaires and micronutrient intake using 24-hour food recall to make it easier for illiterate respondents. The results showed that most respondents were well-informed (58.1%), had micronutrient intake (iron, folic acid, and zinc) in the appropriate category (77.4%), and did not experience anemia (74.2%). The conclusion that there is a relationship between nutritional knowledge and micronutrient intake with the incidence of anemia in pregnant women during the Covid-19 pandemic at the Tapa Health Center, Bone Bolango Regency,Keywords: Nutritional knowledge; Micronutrient intake; Anemia; Pregnant Women; Covid-19 pandemic.